ANALISIS PENGARUH RASIO LEVERAGE, RASIO PROFITABILITAS, RASIO AKTIVITAS, DAN RASIO PASAR TERHADAP RETURN SAHAM PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Faisal Wibisono (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims to determine the effect of Leverage Ratio (DER), Profitability Ratio (ROA and ROE), Activity Ratio (TATO), and the ratio of the Market (EPS) to Stock Return property and real estate companies listed on the Indonesia Stock Exchange year 2010-2014. The independent variables in this study are DER (X1), ROA (X2), ROE (X3), TATO (X4), and EPS (X5). While the variable dependent that Stock Return (Y). This research was conducted with quantitative methods on the financial statements of property and real estate companies during the period 2010-2012. The total sample is 26 companies. Test equipment used to test the research instrument in the form of classical assumption (normality test) and test  BLUE (multicollinearity test, autocorrelation test, and test heteroscedasticity). Testing of the hypothesis is done by multiple linear regression model, the F test and t test.The results of this research indicate that the Leverage Ratio (DER), Profitability Ratio (ROA and ROE), and Activity Ratio (TATO), partially no effect to Stock Return, with the exception of Market Ratios (EPS). Meanwhile, if examined simultaneously, Leverage Ratio, Profitability Ratio, Activity Ratio and Market Ratio that significant effect to Stock Return.  Keywords: Investment, Property and Real Estate, Leverage Ratio, Profitability Ratio, Activity Ratio, Market Ratio, Stock Return.